2000
DOI: 10.1021/bi001814v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Diversity in a Metalloenzyme Superfamily

Abstract: It is now appreciated that the relationships of proteins, particularly enzymes, within a protein superfamily can be understood not only in terms of their sequence similarities and three-dimensional structures but also by chemical threads that relate their functional attributes. The mechanistic ties among superfamily members can often be traced to a common transition state for the rate-limiting step of the reactions being catalyzed. This paper presents an analysis of a metalloenzyme superfamily, the members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
161
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(173 citation statements)
references
References 35 publications
(61 reference statements)
0
161
0
4
Order By: Relevance
“…15−17 Amino acid sequence comparisons have demonstrated that these three enzymes are members of the vicinal oxygen chelate (VOC) superfamily of metalloenzymes. 18 The structural hallmark of this superfamily is a paired βαβββ motif that offers coordination sites to the metal, which in turn help substrate binding through direct coordination. 18 The X-ray structures of FosA from Pseudomonas aeruginosa 13,19 and transposon Tn2921 20 have been solved.…”
Section: Introductionmentioning
confidence: 99%
“…15−17 Amino acid sequence comparisons have demonstrated that these three enzymes are members of the vicinal oxygen chelate (VOC) superfamily of metalloenzymes. 18 The structural hallmark of this superfamily is a paired βαβββ motif that offers coordination sites to the metal, which in turn help substrate binding through direct coordination. 18 The X-ray structures of FosA from Pseudomonas aeruginosa 13,19 and transposon Tn2921 20 have been solved.…”
Section: Introductionmentioning
confidence: 99%
“…5) The third group enzyme is apparently different from the two former groups because it degrades 1,4-or 2,5-dihydroxylated substrates such as gentisate (2,5-dihydroxybenzoate), homogentisate, and hydroquinone. Gentisate 1,2-dioxygenase (GDO, EC1.13.11.4) is included in this group, which cleaves the aromatic ring between the carboxyl and proximal hydroxyl groups in the aromatic ring to yield maleylpyruvate.…”
mentioning
confidence: 99%
“…Outras famílias de glutationa transferases (GSTs), ausentes em mamíferos, são descritas na literatura. 27,28 O sistema de nomenclatura para as GSTs citossólicas e mitocondriais é bem estabelecido 23,29 e prevê que: as glutationa transferases são divididas de acordo com a seqüência de aminoácidos e/ou nucleotídeos, propriedades imunológicas, parâmetros de cinética enzimática e/ou estrutura terciária e quaternária; as sub-unidades devem ser agrupadas segundo a seqüência de seus genes e designadas por algarismos hindu-árabicos numa ordem crescente, em função da data de sua identificação; as sub-unidades codificadas pelo mesmo locus de um gene devem ser designadas pelo mesmo algarismo, sendo as variações alélicas, se observadas, indicadas por letras minúsculas do alfabeto romano em subscrito. 29 Para distinguir enzimas de diferentes espécies, deve-se utilizar a inicial do nome do organismo (termo em inglês) em letra minúscula e em itálico.…”
Section: As Famílias De Glutationa Transferases (Gsts)unclassified
“…Estes compostos são denominados xenobióticos e podem interagir de maneira dele- (26) e da progesterona (28) téria ao organismo. A detoxificação enzimática de xenobióticos pode ser classificada em três fases distintas, porém estritamente relacionadas: fase I, II e III.…”
Section: Metabolismo De Xenobióticos: Detoxificação Ou Bioativação?unclassified
See 1 more Smart Citation